Haplotypic and Genotypic Association of Catechol-O-Methyltransferase rs4680 and rs4818 Polymorphisms and Treatment Resistance in Schizophrenia - Sagud, Marina; Tudor, Lucija; Uzun, Suzana; Perkovic, Matea Nikolac; Zivkovic, Maja; Konjevod, Marcela; Kozumplik, Oliver; Vuksan Cusa, Bjanka; Svob Strac, Dubravka; Rados, Iva; Mimica, Ninoslav; Mihaljevic Peles, Alma; et al. (Frontiers in Pharmacology, 2018)
Treatment-resistant schizophrenia (TRS) continues to be a challenge. It was related to different factors, including alterations in the activity of brain dopaminergic system, which could be influenced by the dopamine-degrading enzyme, catechol-O-methyl-transferase (COMT). Variants of the COMT gene have been extensively studied as risk factors for schizophrenia; however, their association with TRS has been poorly investigated. The aim of the present study was to determine the haplotypic and genotypic association of COMT rs4680 and rs4818 polymorphisms with the presence of TRS. Overall, 931 Caucasian patients diagnosed with schizophrenia (386 females and 585 males) were included, while 270 participants met the criteria for TRS. In males, no significant haplotypic and genotypic associations between COMT rs4680 and rs4818 polymorphisms and TRS were detected. However, genotypic analyses demonstrated higher frequency of COMT rs4680 AA genotype carriers compared to G-allele carriers (p=0.033) and higher frequency of COMT rs4818 CC genotype carriers than G-allele carriers (p=0.014) in females with TRS. Haplotype analyses confirmed that the presence of the G allele in females was associated with lower risk of TRS. In women with TRS, the high activity G-G/G-G haplotype was rare, while carriers of other haplotypes were overrepresented (p=0.009). Such associations of COMT rs4680 and rs4818 high-activity (G variants), as well as G-G/G-G haplotype, with the lower risk of TRS in females, but not in males, suggest significant, but sex-specific influence of COMT variants on the development of treatment-resistance in patients with schizophrenia. However, due to relatively low number of females, those findings require replication in a larger sample.